GIVING REWARD HAVE GREAT IMPACT ON JOBSATISFACTION AND TEACHER COMMITMENT AT SMA SATYA DHARMA BALUNG JEMBER - Maulidah, Iit; Suroso, Imam; Zainollah, Zainollah (MBA : Journal of Management and Business Aplication, 2019)
The title of this research article is "giving reward has great impact onjobsatisfaction and teacher commitmentat SMA Satya Dharma Balung Jember". This study aims to analyze and examine the effect of intrinsic rewards and extrinsic rewards on job satisfaction and teacher commitment in SMA Satya Dharma Balung Jember. This research includes causal, quantitative research, because this study intends to explain causal relationships (causality) between variables through hypothesis testing that has been formulated. The research population is all high school teachers of Satya Dharma Balung Jember. The sampling technique used is Proportional Stratified Random Sampling. The hypothesis proposed in this study is that there is a direct, positive, and significant influence of intrinsic rewards, and extrinsic rewards to job satisfaction and teachers commitment of SMA Satya Dharma Balung Jember. The test validity of research instrument used construct validity. Reliability test was done with Cronbach Alpha. The method of analysis used is path analysis and the calculation process is approached with multiple linear regression analysis. The results showed that intrinsic rewards and extrinsic rewards had a direct, positive, and significant impact on theteacher’s job satisfactionofSatya Dharma Balung Jember high school. Intrinsic rewards, and extrinsic rewards hada direct, positive, and significant impact on the work commitment of SMA Satya Dharma Balung Jember teachers. Intrinsic rewards and extrinsic rewards hadan indirect, positive, and significant impact on teacher commitment, through job satisfaction. Based on the findings of this study, it is expected that the award received in accordance with what is perceived, so that it appears on job satisfaction and ultimately lead to work commitments.